Implementasi Pemberian Remisi Bagi Narapidana di Lembaga Pemasyarakatan Kelas IIa Karawang Dihubungkan Dengan Permenkumham Nomor 7 Tahun 2022 - Dahrul Manalu; Deny Guntara; Muhamad Abas (Peneliti.net, 2023)
ABSTRACT The writing of this scientific work is a form of representation of granting remissions for convicts in class IIA Penitentiary in Karawang Regency based on data findings related to the existing regulations in force in the form of Permenkumham Number 7 of 2022 concerning the Second Amendment Number 3 of 2018 concerning Terms and Procedures for Granting Remission, Assimilation, Visiting Family Leave, Parole, Prior Release Leave, and Conditional Leave as the legal basis for conducting this research. Correctional Institutions as an area that is not only limited by the form of its territory to accommodate convicts, but as a medium that realizes legal objectives by providing guidance and coaching for convicts. In practice, remission itself is one of the convict coaching strategies based on the Regulation of the Minister of Law and Human Rights Number 7 of 2022 which is still valid until 2023. The process of carrying out research is carried out using research methods which in terms of using field data, namely empirical juridical methods in which researchers go to the field and obtain data which will then be processed in this paper. The results of the study show that there has been an increase in the granting of remissions from 2021 to 2022 with data divided into general remissions and special remissions. Keywords: Prisoners, Remissions, Correctional Institutions